2006
DOI: 10.1007/s11426-006-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly behavior of phenyl modified β-cyclodextrins

Abstract: The self-assembly behavior of mono(6-phenolic-6-deoxy)-β-cyclodextrin (1) both in solution and the solid state is comparatively studied by X-ray crystallography and 1 H NMR spectroscopy. The results obtained show that the phenolic groups in the crystal 1 can successively penetrate into the adjacent β-cyclodextrin cavities from the secondary side to form head-to-tail linear polymeric supramolecule with a 2-fold screw axis. The self-assembly behavior also can be determined in D 2 O solution, giving a self-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In particular, we are interested in derivatizing it in order to produce more customized properties. Previously only one earlier report has appeared on phenyl-modified CD (Zhao & Liu, 2006). We have now shown that the click reaction (e.g., Rostovtsev, Green, Fokin, & Sharpless, 2002;Tornøe, Christensen, & Meldal, 2002;Wu & Fokin, 2007) is an alternative (and convenient) method to place a phenyl derivative on CD.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In particular, we are interested in derivatizing it in order to produce more customized properties. Previously only one earlier report has appeared on phenyl-modified CD (Zhao & Liu, 2006). We have now shown that the click reaction (e.g., Rostovtsev, Green, Fokin, & Sharpless, 2002;Tornøe, Christensen, & Meldal, 2002;Wu & Fokin, 2007) is an alternative (and convenient) method to place a phenyl derivative on CD.…”
Section: Introductionmentioning
confidence: 77%
“…It is clear that there is a slight shift upfield for the H-5 peaks. It is well known that such upfield shift is characteristic of the formation of an inclusion compound (e.g., Bilensoy, Vural, Bochot, Renoir, Duchene et al, 2005;Jiang et al, 2007;Zhao, Yang, Hu, & Ma, 2003). Since the phenyl group is hydrophobic, it is not surprising that it gets inserted in the CD cavity.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 For example Harada et al reported about the formation of supramolecular helical polymers, recently. 15 The self-assembly behavior of phenyl modified β-cyclodextrins has been investigated by Liu et al 16 Also self-assembly of gels through shape selective molecular recognition with CD for linear and cyclic guest molecules was investigated on a macroscopic scale very recently. 17 Furthermore there have been few works dealing with self-assembly of chiral compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scientist have been inspired by nature and have investigated various systems mimicking biomolecules by synthetic supramolecular structures with interesting properties and functions. Superstructures formed by hydrogen bonds were reported for the first time by Lehn et al Many contributions about the formation of supramolecular polymers formed by hydrogen bonding can be found in literature. However there have been few works dealing with the self-assembly into supramolecular polymeric structures via host–guest interaction. , For example Harada et al reported about the formation of supramolecular helical polymers, recently . The self-assembly behavior of phenyl modified β-cyclodextrins has been investigated by Liu et al…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most investigations of the self-assembly behavior are to establish control over the preparation of self-assemblies so that their architectures and properties are, at least to some extent, predictable. Thus researchers aim to produce controllable self-assembly by using the wide range of possible intermolecular interactions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Some of these approaches are producing more predictable results.…”
Section: Introductionmentioning
confidence: 99%